RHETORIC AND BALAGHAH: The Significance of Zamakhshari's Contributions to Linguistic Studies - Malik, Khairil; Habibi, Nicolas; Patrah, Ideal (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This article explores the significant contributions of Al-Zamakhshari to the fields of rhetoric and balaghah, and their impact on linguistic studies within the Islamic intellectual tradition. Through his seminal work, Al-Kashshaf, Zamakhshari masterfully integrates linguistic analysis with deep Qur'anic exegesis, showcasing the richness and precision of classical Arabic rhetoric. The article highlights his approach to linguistic beauty, sentence structure, and contextual meaning, which laid a critical foundation for the development of Arabic linguistic theory. Using an analytical-critical method, it also examines how Zamakhshari’s thought influenced subsequent scholars in understanding the intricate relationship between language and meaning in sacred texts. This study reaffirms Zamakhshari’s status as a central figure in the heritage of classical Islamic rhetoric and linguistics.Keywords: Rhetoric, Balaghah, Zamakhshari, Linguistic Studies, Qur'anic Interpretation